Proton Ligand Formation constant and Chelation Tendency of Pyrazinamide - Shrivastava, Sarita; Kumar Gupta, Pradeep (Asian Journal of Chemistry, 2010)
Chelation tendency of pyrazinamide (pyrazine carboxamide) has been worked out and the proton ligand formation constants have been computed using various methods at 30ºC and 0.1 m ionic strength.